The CB2 Agonist β-Caryophyllene in Male and Female Rats Exposed to a Model of Persistent Inflammatory Pain - Ceccarelli, Ilaria; Fiorenzani, Paolo; Pessina, Federica; Pinassi, Jessica; Aglianò, Margherita; Miragliotta, Vincenzo; Aloisi, Anna Maria (Frontiers in Neuroscience, 2020)
Cannabinoids help in pain treatment through their action on CB1 and CB2 receptors. β-caryophyllene (BCP), an ancient remedy to treat pain, is a sesquiterpene found in large amounts in the essential oils of various spice and food plants such as oregano, cinnamon and black pepper. It binds to the CB2 receptor, acting as a full agonist. Sex differences in the BCP-induced analgesic effect were studied by exposing male and female rats to a persistent/repeated painful stimulation. To simulate treatment of a repeated inflammatory condition, after the first formalin-injection (FT1) (50 l, 2.5%), rats received BCP per os for 7 days at two dosages: 5 mg/kg and 10 mg/kg dissolved in olive oil (OIL). The control group was treated with OIL for 7 days. On day 8 the formalin test was repeated (FT2) with a lower formalin concentration (50 l, 1%). During the first and second formalin test, pain induced responses (licking, flexing, paw-jerk) and spontaneous behaviors were recorded and analyzed. In the FT1 (before the beginning of treatment with BCP), females displayed higher pain responses than males during the first part of the test (I phase and interphase), while during the second part (II phase late and early) the values were more similar between the two sexes. In the FT2, pain responses generally decreased in the BCP groups in a dose-dependent manner (i.e. greater effect of BCP 10), with a more pronounced reduction in males than females; moreover, pain responses remained high in the OIL groups and in the female BCP 5 group. In conclusion, long-term intake of BCP appears to be able to decrease pain behaviors in a model of repeated inflammatory pain in both sexes, but to a greater degree in males.